Crystal structure of 5-methyl ß-N-(methylacetyl)methylenedithiocarbazate, C6H10N2OS2 - Tarafder, M.T.H.; Saravanan, N.; Crouse, K.A.; Yamin, B.M.; Fun, H.-K.; Raj, S.S.S.; Razak, I.A. (De Gruyter, 2001)
C6H10N2OS2, monoclinic, P121/n1 (No. 14), a = 4.2699(1) Å, b= 13.7544(2) Å,c= 15.8280(4) Å, β = 97.263(1)°, V= 922A Å3, Z = 4, R(F) = 0.063, wRref(F2) = 0.173, T=293 K.